Análise comparativa entre a aplicação das tecnologias Wi-Fi e ZigBee em estudo de caso: casa inteligente - Maia, Gustavo de Freitas (2022)
The word Domótica results from the junction of the word "domus", which from Latin means house, with the word "robotics", which means automated control of something, it can be defined as a technology or a combination of technologies that allow the automatic management of all housing resources in a "smart" way (FERREIRA and LOPES, 2009). In this context, the present work has the goal to find the advantages and disadvantages of two different wireless home automation systems, by Wi-Fi and ZigBee, applied to the case study of a high standard house, located in Natal-RN, Brazil functionality such as safety, comfort and energy management. The system by ZigBee presented advantages in terms of implementation costs and security, while the system by Wi-Fi proved to be more applicable for its greater consolidation in the market and as a disadvantage, however, identified the need for a more powerful router that would meet the high number of smart devices in your network. Finally, the work concluded that the ZigBee network is the most suitable for the case studied, since it represented higher cost-benefit, in addition to other advantages.